(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article is devoted to the forensic diagnosis of drowning. In addition to the well-known specific features when drowning, special attention is paid to the identification of diatom plankton. The necessity of creating a catalog of diatom plankton of the country’s water bodies was noted.